Common Law Marriage and Couple Formation - Shoshana Grossbard; Victoria Vernon (Institute for the Study of Labor (IZA), 2014)
The Current Population Survey is used to investigate effects of Common Law Marriage (CLM) on whether young US-born adults live in couples in the U.S. CLM effects are identified through cross-state and time variation, as some states abolished CLM over the period examined. Analysis based on Gary Becker's marriage economics helps explain why CLM affects couple formation and does so differently depending on education, sex ratios and parent status. CLM reduces in-couple residence, and more so for childless whites and where there are fewer men per woman. Effects are larger for college-educated men and women without college.
Keywords: J10; J12; J16; 330; Common-Law Marriage; couple; couple formation; marriage; cohabitation; Gary Becker